STUDY ON PARAMETERS INFLUENCING PHASE BEHAVIOR DURING BLOWDOWN OF CO₂-CH₄ MIXTURE FROM CRYOGENIC DISTILLATION COLUMN - SHAFIQ, UMAR (2020)
Cryogenic distillation columns are generally subjected to high-pressure loadings during natural gas purification process. High-pressure conditions inside the column cause safety risk due to potential rupture. When an emergency arises, blowdown is a typical way of minimizing the failure hazard. However, blowdown at cryogenic conditions involves dry ice formation due to the rapid decrease in temperature driven by the Joule-Thomson effect. The dry ice formation intensifies the failure hazard due to orifice blockage. Therefore, optimization of blowdown parameters is necessary to avoid dry ice formation. So far, literature on blowdown of CO₂⎼CH₄ mixture, especially at the cryogenic conditions, is insufficient. In this study, a computational investigation followed by the experimental validation is accomplished to analyze the dry ice formation during blowdown of CO₂⎼CH₄ binary mixture from the cryogenic distillation column. It is noted that composition of mixture, orifice size, and initial conditions inside the vessel have significant impact on blowdown path. For emergency blowdown of binary mixture from -30 °C and 40 bar the optimum orifice size is between 2.00-3.00 mm. Similarly, 5.00 mm orifice is the most suitable orifice size for the planned blowdown from ambient temperature and 40 bar pressure. These orifice sizes don’t promote solidification and discharge the inventory quickly. A correlation, capable to calculate optimum orifice size and blowdown time as a function of initial temperature, pressure, and CO₂ contents, is also developed.